A study of pre-monsoon thunderstorms in Central parts of India - BANERJEE, A. K. (MAUSAM, 1961)
The distribution of average rainfall in a thunderstorm field over central parts of India during the pre-monsoon period (March to May) has been analysed from two different angles. The average distribution of thunderstorms, hailstorms and associated rainfall inside the moist sector in a potential thunderstorm field have also been presented in the paper. The data of all the observatories, including the hydromet observatories, situated in Madhya Pradesh and Vidarbha for the period 1951-57 have been utilised for this study.